THE EFFECT OF MSME FINANCING OF ISLAMIC COMMERCIAL BANKS AND ISLAMIC RURAL BANKS ON ECONOMIC GROWTH IN INDONESIA - Mubarok, Alrojak; Sabiq, Rohmah; Syabani, Raisa; Nurafini, Fira; Canggih, Clarashinta (Proceedings of the International Conference of Islamic Economics and Business (ICONIES); Vol 9 No 1 (2023): The 9th International Conference of Islamic Economics and Business (ICONIES 2023), 2023)
Economic growth is one indication to measure the economy in a country. The MSME sector is one of the sectors with a critical role in economic development in Indonesia. One way to support the MSME sector is through financing, especially Islamic bank financing. Islamic Banking in Indonesia is grouped into Islamic Commercial Banks and Islamic Rural Banks. This study aims to determine the relationship between MSME financing of Islamic commercial and rural banks to economic growth in Indonesia. This study used monthly data for the period 2013-2022. The hypothesis testing used in this study is multiple linear regression. This study found that financing Islamic Commercial Banks and Islamic Rural Banks for the MSME sector significantly affects economic growth in Indonesia.